HUBUNGAN PENGETAHUAN GIZI DAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI PADA PASIEN HIV/AIDS RAWAT JALAN DI RSUD Prof. Dr. W. Z. JOHANNES KUPANG - Sampelimbong, Marissa; Adi, Anak Agung Ayu Mirah; Boro, Regina Maria (Poltekkes Kemenkes Kupang, 2024)
The HIV/AIDS case is a health problem that has occurred globally, including in Indonesia. HIV causes immune dysfunction, leading to malnutrition, and further immune deficiency. Lack of nutritional knowledge and inadequate nutritional intake cause the patient's clinical condition to worsen, thereby increasing the incidence of morbidity and mortality. Good nutritional knowledge accompanied by good nutritional intake for HIV/AIDS patients can be an effort for sufferers to achieve and maintain good nutritional status. The aim of this research was to determine the relationship between nutritional knowledge and macronutrient intake and nutritional status in HIV/AIDS outpatients at Prof. Hospital. Dr. W. Z. Johannes Kupang. This research is a type of analytical descriptive research using a cross sectional study research design. Sampling was taken using the accidental sampling method, the number of samples used the Slovin formula with a total of 35 people. The research results showed that the level of nutritional knowledge was mostly in the poor category at 65.7%. Energy intake in the severe deficit category was 71.4%. Protein intake in the severe deficit category was 25.7%. Fat intake in the severe deficit category was 77.1%. Carbohydrate intake in the severe deficit category was 68.6%. The nutritional status of the majority had normal nutritional status as much as 71.4%. Based on the Chi-Square test, it shows that there is no relationship between nutritional knowledge and nutritional status (p-value=0.530), there is no relationship between macronutrient intake and nutritional status, namely energy intake (p-value=0.568), protein intake (p- value=0.468), fat intake (p-value=0.754), carbohydrate intake (p-value 0.899).